Tmeff2 is expressed in differentiating oligodendrocytes but dispensable for their differentiation in vivo - Hao Huang (Nature Portfolio, 2017)
Abstract Myelin elaborated by oligodendrocytes (OLs) in the central nervous system (CNS) is required for saltatory conduction of action potentials along neuronal axons. We found that TMEFF2, a transmembrane protein with EGF-like and two follistatin-like domains, is selectively expressed in differentiating/myelinating OLs. Previous studies showed that TMEFF2 is capable of binding to PDGFA, which plays important roles in the proliferation, migration and differentiation of oligodendrocyte progenitor cells (OPCs). However, molecular and genetic analysis revealed that Tmeff2 is a weak binder of PDGFA, and not required for OL differentiation and myelin gene expression in vivo. Together, our data suggested that Tmeff2 is specifically upregulated in OLs, but dispensable for OL differentiation and maturation.